2015
DOI: 10.1016/j.cja.2014.12.014
|View full text |Cite
|
Sign up to set email alerts
|

Effect of boundary conditions on downstream vorticity from counter-rotating swirlers

Abstract: Particle image velocimetry (PIV) is utilized to measure the non-reacting flow field in a reflow combustor with multiple and single swirlers. The velocity field, vortex structure and total vorticity levels are experimentally obtained using two different boundary conditions, representing a single confined swirler and multiple swirlers in an annular combustor. The influence of the boundary conditions on the flow field at several locations downstream of the swirlers is experimentally investigated, showing that the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 16 publications
(18 reference statements)
0
1
0
Order By: Relevance
“…As a result, the flame structures and flow fields of multi-nozzle combustors are significantly different from that of the single nozzle combustors [2][3][4][5][6]. Zhang et al [7] conducted a PIV experimental study on the vorticity variation of single-nozzle and three-nozzle combustors, and the results showed that the vorticity of the center nozzle was obviously stronger than that of the single nozzle due to the change of boundary conditions. Villalva et al [8] conducted a study on a multi-nozzle combustor and results showed that the interaction between nozzles could improve combustion stability and reduce emissions.…”
Section: Introductionmentioning
confidence: 99%
“…As a result, the flame structures and flow fields of multi-nozzle combustors are significantly different from that of the single nozzle combustors [2][3][4][5][6]. Zhang et al [7] conducted a PIV experimental study on the vorticity variation of single-nozzle and three-nozzle combustors, and the results showed that the vorticity of the center nozzle was obviously stronger than that of the single nozzle due to the change of boundary conditions. Villalva et al [8] conducted a study on a multi-nozzle combustor and results showed that the interaction between nozzles could improve combustion stability and reduce emissions.…”
Section: Introductionmentioning
confidence: 99%